The Impact of Educational Training on Nurses to improve knowledge about Practices Regarding Patients Safety after Cardiac Catheterization: Educational Training on Nurses about Practices Regarding Patients Safety after Cardiac Catheterization - Saeeda Sania; Raja, .; Ali, Sajid; Ali, Junaid (Pakistan Journal of Health Sciences, 2022)
Cardiac catheterization is a severe health condition that needs standardized care strategies as well as qualified and skilled healthcare professionals to manage it effectively. Objectives: To evaluate the impact of educational training on nurses to improve knowledge about patient safety practices after cardiac catheterization. Methods: This quasi-experimental study was accomplished among nurses working at cardiac units of both genders from March 2021 to September 2021. Non-probability convenience sampling technique was performed for the collection of data. The data was collected by utilizing the open-access structured tool of knowledge and practice. Results: Regarding the level of knowledge, pre-implementation of educational training, the majority of the participant had poor knowledge 15 (30%) and post-educational training, the knowledge level reached good knowledge (70.0 %) and it was also found statistically significant p-value ≤0.000. Similarly, a significant difference between nurses’ practice after the implementation of the educational training shows (66.7%) inadequate practice before the intervention, while (83.3%) of them had an adequate level of practice after the intervention; it is also found to be a significant p-value ≤0.000. Conclusion: The implementation of the educational training for nurses improved knowledge about practices regarding patients’ safety after cardiac catheterization.